Evaluation of the Prevalence of Rheumatoid Factor in Five Regions of Cameroon - Etienne Philemon ATABONKENG; Dieudonné ADIOGO; Essono Mvoa EMMANUEL; Ouambo Fotso HERVÉ; Appolonie MANGA OWONO; Marie Claire OKOMO ASSOUMOU (Archives of Rheumatology, 2015)
Objectives: This study aims to assess the prevalence of rheumatoid factor (RF) of immunoglobulin M nature in the Cameroonian population and the influence of demographic factors on its production. Patients and methods: A total of 369 subjects (125 males and 244 females; mean age 42.36±15.73 years; range 15-88 years) were tested from five regions of Cameroon (Center, East, Far North, Littoral and West) between July 2012 and December 2012. Whole blood was collected from each participant and the serum was used for immunoglobulin M RF assay using the RF-IMMESCO test (agglutination technique). Results: The prevalence of RF in the whole population was 5.4%, with a female to male ratio of 2.4. RF was present in all age groups, but especially in participants of 30 to 60 years of age. The Center region had the highest prevalence (7.5%), while the West region had the lowest prevalence (2.2%). However, there was no significant difference between studied regions (p>0.05). Of the 369 participants tested, 257 (69.6%) complained of having suffered joint pain at one time or another while 112 did not complain of joint pain. The prevalence of RF was 6.22% in the former group and 3.57% in the latter. Among those 50 to 70 years of age, nearly 90% had at least one painful joint. Conclusion: The presence of RF in the study population may lead to joint diseases, which are more common disabling diseases among the inhabitants of Cameroon. Further studies are needed to bring more insight on the prevalence of RF in Cameroon.